HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KREATIVITAS MAHASISWA KEPERAWATAN DI UNIVERSITAS MURNI TEGUH - Ndruru, Novita; Wahyu, Afnijar (Indonesian Trust Nursing Journal, 2025)
Social media is a means where consumers can share various information in the form of text, images, video and audio with other people. Creativity is the interaction between talent, process and environment that a person or group produces products that appear new and useful as defined in a social context. The objective of this study is to determine the relationship between the use of social media and the creativity of nursing students at Murni Teguh University. The Research method is quantitative correlational, the research design analytical survey. The sampling technique used cluster sampling with 152 respondents. Analysis of research data used the Spearman's rho correlation test. The results of this study show that there is a significant relationship between the use of social media and student creativity with a p-value of 0.00 <0.05 and a correlation coefficient of 0.485**. It is concluded that there is a significant relationship between the use of social media and the creativity of nursing students at Murni Teguh University. It is recommended for future researchers to add other variables such as personality, e-learning learning methods, and the negative impact of social media on students, business day home care training, business management skills, interest in entrepreneurship.